2018
DOI: 10.1200/jgo.17.00098
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Breast Cancer Early Detection Training on Rwandan Health Workers’ Knowledge and Skills

Abstract: PurposeIn April 2015, we initiated a training program to facilitate earlier diagnosis of breast cancer among women with breast symptoms in rural Rwanda. The goal of this study was to assess the impact of the training intervention in breast cancer detection on knowledge and skills among health center nurses and community health workers (CHWs).MethodsWe assessed nurses’ and CHWs’ knowledge about breast cancer risk factors, signs and symptoms, and treatability through a written test administered immediately befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 21 publications
(25 reference statements)
0
28
0
1
Order By: Relevance
“…Efforts to improve early detection of breast cancer have focused on educating community health care workers in performing clinical breast examinations and using appropriate referral protocols. 18 These training programs are being expanded across the country. Further improvements in early detection of breast cancer will include reducing the delay from presentation to diagnosis by expanding breast imaging capabilities for symptomatic and high-risk individuals and increasing the number health care professionals trained to recognize early signs and symptoms of the disease.…”
Section: Cancer Prevention Early Detection and Screeningmentioning
confidence: 99%
“…Efforts to improve early detection of breast cancer have focused on educating community health care workers in performing clinical breast examinations and using appropriate referral protocols. 18 These training programs are being expanded across the country. Further improvements in early detection of breast cancer will include reducing the delay from presentation to diagnosis by expanding breast imaging capabilities for symptomatic and high-risk individuals and increasing the number health care professionals trained to recognize early signs and symptoms of the disease.…”
Section: Cancer Prevention Early Detection and Screeningmentioning
confidence: 99%
“…36 Importantly, 63% (n=10/16) of studies had solely female CHWs. 2 33-36 38 39 43 44 46 Only one study from Rwanda, by Pace et al, 42 provided a detailed description regarding the characteristics of the CHWs, as well as their responsibilities beyond breast health. 42 In this study, CHWs (62% of who were female) were described as playing several roles, including building community awareness about preventive healthcare and connecting individuals to the wider healthcare system.…”
Section: Results Search Resultsmentioning
confidence: 99%
“…2 34 44 One study did not specifically describe a role for CHWs in a screening or early diagnosis programme but rather provided an in-depth assessment of a training programme designed for CHWs to assist in early detection more generally and was thus deemed appropriate for inclusion in the final review. 42 In the studies where early diagnosis was selected over general population screening, methods including 'case finding' were deemed more appropriate given the low incidences of breast cancer, young age of onset and difficulty in follow-up from initial presentation. In all 16 studies, CHWs had a variety of different roles in early detection initiatives.…”
Section: How Are Chws Currently Deployed In Breast Cancer Early Detecmentioning
confidence: 99%
“…35 Other studies have also demonstrated the efficacy of training community health workers in the early detection and referral of breast and cervical cancer. [35][36][37][38][39][40][41] Whether such interventions in the adult cancer space can translate effectively to improvments in the early detection of childhood cancers in LMICs is a subject for future research. is thus dependent on cancer type and jurisdiction.…”
Section: Discussionmentioning
confidence: 99%